2014 IEEE International Conference on Smart Grid Communications (SmartGridComm) 2014
DOI: 10.1109/smartgridcomm.2014.7007760
|View full text |Cite
|
Sign up to set email alerts
|

A first look at machine-to-machine power grid network traffic

Abstract: The purpose of network traffic characterization is to explore unknown patterns in different types of network communications to help improve many aspects of the network. While many previous studies have explored the characterization of many different networks (e.g., university networks), the power grid network (and other SCADA networks) characterization has not yet been studied. In this paper, we provide a characterization of the power grid network to answer questions like the following: i) how stable is the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…When we ran our analysis again over a dataset with a longer duration (6 months vs 2 months) for the same device that was noted in previous research [7], the distribution of ISNs again showed very distinct clusters, as in Figure 2a. However, when we looked closer at the ISN generation shown in Figure 2b, there was no clear pattern or dependence on time, suggesting the use of a very weak pseudo random generator.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…When we ran our analysis again over a dataset with a longer duration (6 months vs 2 months) for the same device that was noted in previous research [7], the distribution of ISNs again showed very distinct clusters, as in Figure 2a. However, when we looked closer at the ISN generation shown in Figure 2b, there was no clear pattern or dependence on time, suggesting the use of a very weak pseudo random generator.…”
Section: Resultsmentioning
confidence: 57%
“…After an initial characterization of the dataset [7] suggested that some devices had uneven distributions of TCP ISNs, the issue of TCP ISN generation was studied in more detail. Since the outdated original TCP specifications recommended the use of a clock-based generation algorithm [12], the dataset was first analyzed to see if there was any relationship between time and the ISNs generated.…”
Section: Methodsmentioning
confidence: 99%
“…Much of the limited research that has taken place in the SCADA domain was released in 2012 and found that the traffic of a water distribution facility was unlike that of a typical IT network [2]. In addition to this, research was published in 2014 that provided a high-level look at power substation traffic [21]. Then in 2017, an in-depth study was published that provided a more detailed characterization [15] of behavior across multiple substations and discussed methods to improve TCP for ICS networks.…”
Section: Related Workmentioning
confidence: 99%
“…In a separate work [4], Barbosa et al compared the SCADA traffic with SNMP traffic and showed that both traffic types exhibit periodical behavior, as a consequence of the polling mechanism used to retrieve data. In 2014, Jung et al [11] characterized the traffic of a power station network with variations in frame size, TCP connections, TCP ephemeral port number, and TCP initial sequence number. Formby et al [8] characterized the traffic from the same environment and found TCP vulnerabilities in power grid devices.…”
Section: Related Workmentioning
confidence: 99%